The Load Alternation: Semantic Shifts and Implicit Arguments - Lumsden, John (Revue québécoise de linguistique, 1994)
ABSTRACTThis study argues that verbal expressions like to load, to pack, to pile, etc. are composed of specific substantive concepts and general predicate concepts. All surface expressions involve a derivation that combines these elements. Substantive concepts may also appear in nominal expressions (e.g. a load, a pack, a pile, etc.). The verbal expressions allow an alternate realization of their argument structure because the interpretation of the substantive concept undergoes a semantic shift so that it combines differently with the pertinent predicate concepts. In one realization, the substantive concept is an implicit theme argument; in the other, it is an implicit location.